Implementation of Samsung Tech Institute Program in SMK Negeri 2 Bawang, Banjarnegara Regency - Hartantri, Anjuni Maulia; Linggarwati, Tundjung (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2024)
This research aims to determine the implementation of the Samsung Tech Institute Program which is Corporate Social Responsibility (CSR) from a multinational company, namely Samsung, especially at SMK Negeri 2 Bawang, Banjarnegara Regency. This research uses CSR as a framework analysis that uses the Triple Bottom Line principle. The method is a descriptive qualitative, with primary data sources from interviews and observations as well as secondary data. The research results show that the Samsung Tech Institute Program is implemented through Samsung Indonesia's CSR activities